The Museum of European Cultures of the Staatliche Museen zu Berlin as a Platform of Intercultural Dialogue - Konrad Vanja; Elisabeth Tietmeyer (Journal of Ethnology and Folkloristics)
Presentation at the Centenary of the Estonian National Museum, Tartu, 13 April 2009.